Kinematic modelling of swimmers' impulse and flight phases during a grab start - Houel, N.; Rey, J. L.; Lecat, S.; Hellard, P. (First international symposium sciences and practices in swimming, 2006)
Under race conditions, the Start directly influences an athlete's performance. Specific parameters relative to the start are difficult to analyse, other than by comparing swimmers' movements with kinematics values. The model developed through in the course of the work presented hereafter aimed to predict swimmers1 performance during the impulse and airborne phases of the grab Start, based on the parameters available to coaches. Despite simplified assumptions and the experimental conditions used by trainers, this model defines kinematics values (instant of takeoff, flight distance, etc.) with acceptable precision (<5%). Future developments, within the next years, will enable the model to simulate swimmers' movements in order to optimize their impulse and their airborne phases.